Impact of Information Services through the Application for Quick Information Service Assistant for Class II District Court, Tanah Grogot Regency, Paser Regency - Bambang Irawan; Achmad Fikri (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This article describes the impact of achieving the goals of bureaucratic reform through the following aspects: transparency, reducing administrative corruption, improving services, and empowerment by using the Quick Information Service Assistant application at the Class II District Court Office, Tanah Grogot Regency. The problem is focused on the impact of using the ALICE application. To approach this problem, a theoretical reference is used (Indrayani, 2020) that e-Government applications have shown an impact on the goals of public sector reform through information disclosure for the public, service transparency, increasing community participation. have an impact on reducing corruption, increasing accessibility and empowering the public. The implementation of the ALICE application is still at the emerging stage in terms of e-Government implementation, while the level of innovation is in the first stage, namely e-information. The data were collected through interview techniques, observations, and literature studies and analyzed through interactive model data analysis techniques (Miles et al., 2014). This article concludes that the Quick Information Service Assistant Application has provided essential information for the public regarding requests for ticket fines, requests for certificates, information on the trial agenda, information on fees and remaining down payments, court fees, and information on the Supreme Court e-court. The positive impact felt by the presence of the Rapid Information Service Assistant, namely increasing service transparency and encouraging active community participation. Then the impact in reducing the occurrence of administrative corruption occurs because there is no meeting between the public and officers. In contrast, in the aspect of improving the quality of service, the public does not need to spend transportation costs to get information. Aspects of empowerment, namely the existence of feedback from the public in services, will be able to improve the quality of information and good collaboration and reduce the practice of brokering. the public does not need to spend transportation costs to get information. Aspects of empowerment, namely the existence of feedback from the public in services, will be able to improve the quality of information and good collaboration and reduce the practice of brokering. the public does not need to spend transportation costs to get information. Aspects of empowerment, namely the existence of feedback from the public in services, will be able to improve the quality of information and good collaboration and reduce the practice of brokering.